Effect of retained chlorine in ENCAT™ 30 catalysts on the development of encapsulated Pd: insights from in situ Pd K, L3 and Cl K-edge XAS. (2nd October 2017) - Newton, Mark. A.; Nicholls, Rachel; Brazier, John B.; Nguyen, Bao N.; Mulligan, Christopher J.; Hellgardt, Klaus; Barreiro, Elena M.; Emerich, Hermann; Hii, King Kuok (Mimi); Snigireva, Irina; Thompson, Paul B. J.
Abstract: In situ X-ray absorption spectroscopy (XAS) and Pd K, LIII, and Cl K-edges shows that Cl can be present in significant amounts in ENCAT™ 30 catalysts and that it can severely retard Pd nanoparticle (NP) development in flowing solvents. We also show that whilst polymeric encapsulation protects the Pd against solvent induced agglomeration of Pd nanoparticles the evidence suggests it does not prevent the formation PdHx through reaction with the aqeous ethanol solvent, and that, as received, ENCAT™ 30 NP catalysts are not, for the most part, comprised of nanoparticulate Pd 0 irrespective of the presence of Cl. Abstract :